2023
DOI: 10.20473/amnt.v7i1.2023.20-26
|View full text |Cite
|
Sign up to set email alerts
|

Asupan Zinc Berpengaruh pada Stunting Balita : Studi Belah Lintang pada Balita Usia 3 Tahun

Abstract: Latar Belakang: Balita stunting di Indonesia masih menjadi perhatian pemerintah. Kemenkes RI mencatat angka stunting 2020 adalah 27,7% menjadi 24,4% di tahun 2021, sedangkan target pemerintah tahun 2024 adalah 14%. Tujuan: Tujuan utama penelitian adalah membuktikan korelasi antara asupan Zinc dengan rerata pertumbuhan tinggi badan balita dan hubungan asupan Zinc dengan stunting. Metode: Penelitian belah lintang 54 Balita usia 3 tahun, riwayat kelahiran di RSI Sultan Agung dan Puskesmas Bangetayu bulan Agustus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The results of a previous study have shown that mothers' education and socioeconomic status are not directly linked to stunting. Still, babies' daily nutritional intake is associated with stunting at the age of three 17 . Based on the Chi-Square test results, the data on mothers' education, family income, and full vaccination history using Fisher's exact test had p-values of 0.031, 0.000, and 0.000, respectively, with p<0.05 indicating significant differences in terms of mothers' education, family income, and full vaccination history between the intervention and control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a previous study have shown that mothers' education and socioeconomic status are not directly linked to stunting. Still, babies' daily nutritional intake is associated with stunting at the age of three 17 . Based on the Chi-Square test results, the data on mothers' education, family income, and full vaccination history using Fisher's exact test had p-values of 0.031, 0.000, and 0.000, respectively, with p<0.05 indicating significant differences in terms of mothers' education, family income, and full vaccination history between the intervention and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, mothers' knowledge affects their attitude and behavior in selecting food for their babies; good nutritional knowledge potentially leads to better food consumption for babies 20 . An increase and change in mothers' knowledge, attitudes, and behavior after counseling can then positively affect the provision of nutritious food for their children, so children could have better food consumption, which expectedly leads to weight and length increments 17 .…”
Section: Resultsmentioning
confidence: 99%